Topographical and pathotopographical medical atlas of the human body - Seagal, Z. M. 1944- (John Wiley & Sons, Inc. ; Scrivener Publishing LLC, 2020)
"Medicine is an ever-changing and rapidly evolving science, and new methods and techniques are being discovered and pioneered all the time. Medical atlases like this one, and the great classic, Gray's Anatomy, are extremely important not only to teach less experienced physicians and medical students the basics, but also to the veteran physician as a reference. Using the same technology and combining the four previous atlases by the same author, solves the problem of visualization of topographical and pathotopographical anatomy for the entire human body . Combines all four of the author's previous books, Ultrasonic Topographical and Pathotopographical Anatomy and its sequels, covering the entire human body in its scope .Goes beyond previous attempts, which are often drawings, by using state-of-the-art technology to show detailed physiological areas . Is for medical professionals of all types and levels, from students and professors to working doctors and other medical professionals doing research and development"- Resumé vydavatel
Keywords: anatomie člověka; ultrazvuková tomografie; ultrasonografie; human anatomy; ultrasonic tomography; ultrasonography; elektronické knihy; atlasy; electronic books; atlases